Evaluation of Kidney Function in Patients on Chemotherapy - Haziyev, Elgun; GÜRSU, Meltem; GÜRSU, MELTEM; ŞEKER, Mesut; ŞEKER, MESUT; ELÇİOĞLU, Ömer Celal; ELÇİOĞLU, ÖMER CELAL; ARTAN, AYŞE SERRA; ARTAN, AYŞE SERRA; ALİYEV, Altay; ALİYEV, ALTAY; TÜRK, HACI MEHMET; et al. (My University, 2021)
Objective: We aimed to study whether long-term kidney function would be affected by different chemotherapy regimens in patients with malignancy.